MODEL KURIKULUM PENDIDIKAN AGAMA ISLAM DI SD ISLAM AL-AZHAR (SINERGI ANTARA KURIKULUM NASIONAL DAN NILAI-NILAI ISLAM) - Maulida, Nabila Putri (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
ABSTRACT Islamic Religious Education (PAI) in Indonesia plays an important role in shaping the character and morals of students from an early age. In the context of basic education, integration between the national curriculum and Islamic values ??is a challenge in itself especially in facing developments in science, technology, and demands for global competence. Al-Azhar 9 Islamic Elementary School Kemang Pratama is an educational institution that has developed a curriculum model that combines the National Curriculum, Islamic values, ??and the Cambridge International Curriculum. This research aims to analyze the Islamic Religious Education (PAI) curriculum model at Al-Azhar 9 Islamic Elementary School Kemang Pratama. This research also explores the synergy between the national curriculum and the Islamic-based curriculum in the planning, implementation, and evaluation aspects. The research method uses a qualitative approach with a case study method. Data was collected through observation, interviews, and documentation and then analyzed using data reduction techniques, data presentation, and drawing conclusions. The research results show that the curriculum at at Al-Azhar 9 Islamic Elementary School Kemang Pratama has succeeded in integrating Islamic values ??into the national curriculum through holistic learning programs, the use of technology, and strengthening character education. Intracurricular activities such as morning tadarus and memorizing the Qur'an, as well as extracurricular activities such as the art of reading the Qur'an and little preachers, support students' spiritual and academic development. However, there are challenges in the form of lagging behind in memorization for some students, a lack of role for some parents, and the limited ability of some teachers to utilize technology. This research contributes to the development of a curriculum model based on Islamic values ??in elementary schools. The results of this research are limited to the context of the Al-Azhar 9 Islamic Elementary School Kemang Pratama, so further studies are needed in other schools to expand the generalization. ABSTRAK Pendidikan Agama Islam (PAI) di Indonesia memegang peranan penting dalam membentuk karakter dan moral peserta didik sejak usia dini. Dalam konteks pendidikan dasar, integrasi antara kurikulum nasional dan nilai-nilai Islam menjadi tantangan tersendiri, terutama dalam menghadapi perkembangan ilmu pengetahuan, teknologi, serta tuntutan kompetensi global. SD Islam Al-Azhar 9 Kemang Pratama merupakan salah satu lembaga pendidikan yang telah mengembangkan model kurikulum yang memadukan Kurikulum Nasional, nilai-nilai Islam, dan Kurikulum Internasional Cambridge. Penelitian ini bertujuan untuk menganalisis model kurikulum Pendidikan Agama Islam (PAI) di SD Islam Al-Azhar 9 Kemang Pratama. Penelitian ini juga mengeksplorasi sinergi antara kurikulum nasional dan kurikulum berbasis Islam dalam aspek perencanaan, pelaksanaan, dan evaluasi. Metode penelitian menggunakan pendekatan kualitatif dengan metode studi kasus. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi, kemudian dianalisis menggunakan teknik reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa kurikulum di SD Islam Al-Azhar 9 Kemang Pratama berhasil mengintegrasikan nilai-nilai Islam dalam kurikulum nasional melalui program pembelajaran holistik, penggunaan teknologi, dan penguatan pendidikan karakter. Kegiatan intrakurikuler seperti tadarus pagi dan hafalan Al-Qur'an, serta kegiatan ekstrakurikuler seperti seni baca Al-Qur'an dan da'i cilik, mendukung pengembangan spiritual dan akademik siswa. Namun, terdapat tantangan berupa ketertinggalan hafalan beberapa siswa, kurangnya peran sebagian orang tua, dan keterbatasan kemampuan beberapa guru dalam memanfaatkan teknologi. Penelitian ini memberikan kontribusi bagi pengembangan model kurikulum berbasis nilai-nilai Islam di sekolah dasar. Hasil penelitian ini terbatas pada konteks SD Islam Al-Azhar 9 Kemang Pratama, sehingga perlu studi lebih lanjut di sekolah lain untuk memperluas generalisasi.